Analysis of web scraping techniques to get keywords suggestion and allintitle automatically from Google Search Engines - Aris Wahyu Murdiyanto; Adri Priadana; Aris Wahyu Murdiyanto (Institut Teknologi Dirgantara Adisutjipto, 2021)
Keyword research is one of the essential activities in Search Engine Optimization (SEO). One of the techniques in doing keyword research is to find out how many articles titles on a website indexed by the Google search engine contain a particular keyword or so-called